2011
DOI: 10.1037/a0023921
|View full text |Cite
|
Sign up to set email alerts
|

Thinking can cause forgetting: Memory dynamics in creative problem solving.

Abstract: Research on retrieval-induced forgetting has shown that retrieval can cause the forgetting of related or competing items in memory (Anderson, Bjork, & Bjork, 1994). In the present research, we examined whether an analogous phenomenon occurs in the context of creative problem solving. Using the Remote Associates Test (RAT; Mednick, 1962), we found that attempting to generate a novel common associate to 3 cue words caused the forgetting of other strong associates related to those cue words. This problem-solving-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
78
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 19 publications
9
78
1
Order By: Relevance
“…Although misleading associates may interfere with a participant's ability to retrieve a solution initially, an incubation period may reduce access to those interfering items and thus facilitate access to the hidden solution. Storm and colleagues have suggested that problem solvers may also have the capacity to overcome fixation during problem solving by actively inhibiting, and thus forgetting, fixation-inducing associates (Storm & Angello, 2010;Storm, Angello, & Bjork, 2011; for a review see Storm, 2011a). One finding that sup-ports this hypothesis is the correlation between RAT problem solving and retrieval-induced forgetting (Storm & Angello, 2010).…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…Although misleading associates may interfere with a participant's ability to retrieve a solution initially, an incubation period may reduce access to those interfering items and thus facilitate access to the hidden solution. Storm and colleagues have suggested that problem solvers may also have the capacity to overcome fixation during problem solving by actively inhibiting, and thus forgetting, fixation-inducing associates (Storm & Angello, 2010;Storm, Angello, & Bjork, 2011; for a review see Storm, 2011a). One finding that sup-ports this hypothesis is the correlation between RAT problem solving and retrieval-induced forgetting (Storm & Angello, 2010).…”
Section: Introductionmentioning
confidence: 93%
“…For example, just as retrieval success is not a necessary condition for retrieval-induced forgetting (Storm, Bjork, Bjork, & Nestojko, 2006;Storm & Nestojko, 2010), problem-solving success is not a necessary condition for problem-solving-induced forgetting (Storm et al, 2011). Attempting to solve problems caused participants to forget fixating associates even when those attempts failed.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations